Patterns and Trends of the Mortality From Bone Cancer in Pudong, Shanghai: A Population-Based Study - Ma, Gui-Fen; Bao, Qi-Yuan; Zhang, Hong-Yue; Chen, Yi-Chen; Zhang, Yue; Jiang, Zhao-Yong; Li, Xiao-Pan; Zhang, Ju-Hua (Frontiers in Oncology, 2022)
Introduction: The burden of cancer-related mortality of common malignancies has been reported in the worldwide. However, whether bone cancer (BC), as a highly aggressive and heterogeneous group of rare cancers, followed a similar or distinct epidemiolocal pattern during such process remains largely unknown. We aimed to analyze the mortality and the temporal trends of BC in relation to gender, age, and premature death in Shanghai,China. Methods: We conducted a population-based analysis of the mortality data of BC in PNA from 2005 to 2020. The epidemiological characteristics and long-term trends in crude mortality rates (CMR), age-standardized mortality rates worldwide (ASMRW), and rate of years of life lost (YLL) were analyzed using the Joinpoint regression program. The demographic and non-demographic factors affecting the mortality rate were evaluated by the decomposition method. Results: There are 519 BC-specific deaths accounting for 0.15% of all 336,823 deaths and 0.49% of cancer-specific death in PNA. The CMR and ASMRW of BC were 1.15/10^5 person-year and 0.61/10^5 person-year, respectively. The YLL due to premature death from BC was 6,539.39 years, with the age group of 60–69 years having the highest YLL of 1,440.79 years. The long-term trend of CMR, ASMRW and YLL rate significantly decreased by -5.14%, -7.64% and -7.27% per year (all P < 0.05) in the past 16 years. However, the proportion of BC-specific death within the total cancer-specific death dropped to a plateau without further improvement since 2016, and a remarkable gender and age disparity was noticed in the observed reduction of mortality. Specifically, the elderly benefited less but accounted for a larger percentage of BC population in the last decades. Although the overall mortality of BC decreased, there was still a significant upward trend toward an increased mortality rate caused by the aging of the BC patients. Conclusion: Our study provides novel insights on the epidemiological characteristics and longitudinal dynamics of BC in a fast urbanization and transitioning city. As a rare disease affecting all ages, the burden of BC among the elderly emerged to form an understudied and unmet medical need in an aging society.